The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00213-003-1445-7
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion enhances brain reward function and reverses the affective and somatic aspects of nicotine withdrawal in the rat

Abstract: Bupropion acts on multiple levels to alter brain reward circuits influenced by nicotine, in addition to reducing the expression of somatic signs of withdrawal. First, bupropion, unlike other antidepressants, increases brain reward function under baseline conditions in non-withdrawing subjects. Second, at low doses bupropion blocks the rewarding effects of nicotine. Third, bupropion reverses the negative affective aspects of nicotine withdrawal. Such actions are likely to act in concert to mediate the unique an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
2
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(171 citation statements)
references
References 72 publications
11
155
2
3
Order By: Relevance
“…Research has shown that bupropion may facilitate smoking cessation by reducing some symptoms of nicotine withdrawal, such as somatic symptoms or alterations of reinforcement and reward Cryan et al, 2003). However, the effects of bupropion on deficits in learning and memory that occur during nicotine withdrawal remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that bupropion may facilitate smoking cessation by reducing some symptoms of nicotine withdrawal, such as somatic symptoms or alterations of reinforcement and reward Cryan et al, 2003). However, the effects of bupropion on deficits in learning and memory that occur during nicotine withdrawal remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cryan and colleagues (2003) reported that a low dose of bupropion blocked the acute nicotine enhancement of ICSS and also reversed the decrease in ICSS when rats were withdrawn from chronic nicotine. In addition, rats withdrawn from chronic nicotine exhibited somatic signs of nicotine withdrawal such as writhing or abdominal constrictions, and bupropion dose-dependently reversed these symptoms (Cryan et al, 2003;Malin et al, 2006). Malin and colleagues (2006) have also found that bupropion can reverse nicotine withdrawal-related conditioned place aversion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Withdrawal-related decreases in the brain reward system in humans has been modeled using the intracranial self stimulation (ICSS) procedure, in which rats press a lever to deliver electrical stimulation to reward-related brain areas. Nicotine withdrawal increases ICSS threshold [26,81,156]. Thus, several nicotine withdrawal symptoms reported in humans have been modeled and studied in rodents.…”
Section: Nicotinic Acetylcholine Receptors: Animal Researchmentioning
confidence: 99%
“…The rats were habituated to the observation chamber for 5 minutes per day on 3 consecutive days prior to testing. The following somatic signs were recorded based on checklist of nicotine abstinence signs: body shakes, cheek tremors, escape attempts, eye blinks, gasps, genital licks, head shakes, ptosis, teeth chattering, writhes and yawns (Cryan et al, 2003;Malin et al, 1992). Ptosis was counted once per minute if present continuously.…”
Section: Somatic Withdrawal Signsmentioning
confidence: 99%